The crystal structure of 2,5-bis[(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)amino]cyclohexa-2,5-diene-1,4-dione, C28H26N6O4 - Smith Mark G.; Lemmerer Andreas (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C28H26N6O4, monoclinic, P21/n (no. 14), a = 13.0398(4) Å, b = 7.1786(2) Å, c = 14.9824(5) Å, β = 112.642(2)°, V = 1294.37(7) Å3, Z = 2, Rgt(F) = 0.0458, wRref(F2) = 0.1133, T = 173 K.